Optical Frequency Comb Generation and Further Advances From the Photonics Community in Serbia and Western Balkans - Marko M. Krstic; Jasna V. Crnjanski; Dejan M. Gvozdic (IEEE Photonics Journal)
The article presents a short statistical overview of photonics research in the Western Balkans, with more spotlight aimed at the field of optical frequency combs with focus on the overview of the research conducted at the University of Belgrade-School of Electrical Engineering. We give a review of proposed schemes for single and dual optical frequency combs generation, based on optimized gain-switching and electro-optic modulator operation and expand our previous results with analytical approximations for comb lines intensities for the gain-switched laser.